2018
DOI: 10.3168/jds.2018-14598
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to antimicrobials through the milk diet or systemic therapy is associated with a transient increase in antimicrobial resistance in fecal Escherichia coli of dairy calves

Abstract: The objective of this prospective cohort study was to describe the relationship between exposure to antimicrobials, through both the milk diet and systemic therapy, and to describe antimicrobial resistance of fecal Escherichia coli in dairy calves pre- and postweaning. A convenience sample of 15 Minnesota dairy farms was chosen, representing 3 equal cohorts of milk diet fed to preweaned calves: medicated milk replacer (MMR), nonmedicated milk replacer (NMR), or pasteurized nonsaleable milk (PNM). Five newborn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
3
10
1
1
Order By: Relevance
“…Berge et al [17] demonstrated that fecal pathogens shed by pre-weaned calves show an increase in AMR when the animals are exposed to prophylactic treatments with AMD, particularly ones added to milk replacer. A study conducted in Minnesota [26] showed similar results of transient resistance as this study does. Foutz et al [26] evaluated the AMR score (given to the isolate according to the number of antimicrobial classes to which it was resistant) between calves and observed that calves fed with medicated milk replacer had a higher AMR score than the calves fed unmedicated milk replacer.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Berge et al [17] demonstrated that fecal pathogens shed by pre-weaned calves show an increase in AMR when the animals are exposed to prophylactic treatments with AMD, particularly ones added to milk replacer. A study conducted in Minnesota [26] showed similar results of transient resistance as this study does. Foutz et al [26] evaluated the AMR score (given to the isolate according to the number of antimicrobial classes to which it was resistant) between calves and observed that calves fed with medicated milk replacer had a higher AMR score than the calves fed unmedicated milk replacer.…”
Section: Discussionsupporting
confidence: 83%
“…A study conducted in Minnesota [26] showed similar results of transient resistance as this study does. Foutz et al [26] evaluated the AMR score (given to the isolate according to the number of antimicrobial classes to which it was resistant) between calves and observed that calves fed with medicated milk replacer had a higher AMR score than the calves fed unmedicated milk replacer. The resistance was transient resolving after weaning (at week 16), suggesting that once the antimicrobial pressure was removed there was a re-establishment of the susceptible E. coli bacteria [26].…”
Section: Discussionsupporting
confidence: 83%
“…Other authors have determined the effect of systemic antimicrobials on the fecal microbiome and antimicrobial resistance among fecal microbiota of dairy cattle (Tragesser et al, 2006;Chambers et al, 2015), dairy calves (Foutz et al, 2018), and beef cattle (Ferguson et al, 2018;Holman et al, 2019). Similar to what was found herein with intramammary pirlimycin administration, some of these studies also found that the changes in fecal microbiota were temporary (Ferguson et al, 2018;Foutz et al, 2018).…”
Section: Discussionsupporting
confidence: 61%
“…Other authors have determined the effect of systemic antimicrobials on the fecal microbiome and antimicrobial resistance among fecal microbiota of dairy cattle (Tragesser et al, 2006;Chambers et al, 2015), dairy calves (Foutz et al, 2018), and beef cattle (Ferguson et al, 2018;Holman et al, 2019). Similar to what was found herein with intramammary pirlimycin administration, some of these studies also found that the changes in fecal microbiota were temporary (Ferguson et al, 2018;Foutz et al, 2018). More specifically, when evaluating the fecal microbiome of dairy cows treated with subcutaneously administered ceftiofur crystalline free acid sterile suspension compared with untreated controls, treated cows tended to have an increased abundance of Bacteroidia and a decrease in class Actinobacteria compared with control cows 3 d posttreatment (Chambers et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the consequences of antimicrobial resistance in dairy pathogens potentially impacting human health are residual as long as safety measurements are applied and milk pasteurized (Oliver et al, 2010). However, several studies, demonstrated an increased prevalence of resistant bacteria in commensal populations from dairy animals undergoing antibiotic treatment (Foutz et al, 2018; Springer et al, 2018). Additionally, a common practice is to use non-salable milk from cows treated with antibiotics to feed young calves which carries the risk of increasing fecal shedding of AMR bacteria.…”
Section: Introductionmentioning
confidence: 99%